1996
DOI: 10.1016/s0022-5223(96)70378-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival benefits of coronary artery bypass grafting and percutaneous transluminal angioplasty in patients with coronary artery disease

Abstract: The purpose of this study was to evaluate long-term survival benefits of bypass surgery and angioplasty versus medical therapy in 9263 patients at Duke University Medical Center between 1984 and 1990 with coronary artery disease confirmed by cardiac catheterization to involve one, two, or three vessels. Clinical data were prospectively entered into an established cardiovascular database, and annual follow-up was 97% complete for a mean interval of 5.3 years and a maximal interval of 10 years. Outcomes were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0
10

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(110 citation statements)
references
References 12 publications
3
97
0
10
Order By: Relevance
“…For example, long-term survival with 97% follow-up for 9263 patients with CAD has been reported by the Duke Registry. 24 Over a spectrum of baseline risk, CABG was associated with improved long-term outcomes in comparison with medical therapy among patients in moderateand high-risk strata, and PTCA was superior to medical therapy only among low-risk strata. 24 Compared with PTCA, CABG was associated with improved outcomes among highrisk strata (chiefly those with involvement of the proximal left anterior descending artery), and PTCA was superior to CABG among low-risk patients.…”
Section: Database Studiesmentioning
confidence: 96%
“…For example, long-term survival with 97% follow-up for 9263 patients with CAD has been reported by the Duke Registry. 24 Over a spectrum of baseline risk, CABG was associated with improved long-term outcomes in comparison with medical therapy among patients in moderateand high-risk strata, and PTCA was superior to medical therapy only among low-risk strata. 24 Compared with PTCA, CABG was associated with improved outcomes among highrisk strata (chiefly those with involvement of the proximal left anterior descending artery), and PTCA was superior to CABG among low-risk patients.…”
Section: Database Studiesmentioning
confidence: 96%
“…RCTs comparing PCI and CABG for multivessel CAD did not demonstrate a statistically significant survival difference (5-16), with the exception of patients with diabetes (17).…”
Section: Pci Versus Cabgmentioning
confidence: 96%
“…This patient population is one of the most controversial, from an outcome perspective. Early registry studies comparing PTCA and CABG showed a trend toward improved survival following surgical revascularization in this patient population (17)(18)(19)(20)(21). However, RCTs from the PCI era, which used stents and GP IIb/IIIa inhibitors, are conflicting.…”
Section: Pci Versus Cabgmentioning
confidence: 99%
See 2 more Smart Citations